Style Matters: Explaining the Gender Gap in the Price of Paintings - Savolainen, Savolainen (Österreichische Zeitschrift für Geschichtswissenschaften, 2006)
The purpose of this study is to describe and explain gender differences in the price of paintings by contemporary American artists. In our data, the average price of a painting by a female artist is about 25 percent lower than the price of a painting by a male artist. This finding suggests that the monetary appraisal of artistic work is firmly embedded in the system of gender stratification characterizing the labor mar- ket at large. Drawing on two supply-side theories – the human capital perspective and the pre-market socialization hypothesis – we estimate a series of multivariate models in an attempt to identify sources of the observed gender difference. The artistic style proved to be the only variable that explained a non-trivial amount of the price difference between men and women. As most of the disparity remains unexplained, our findings do not rule out the assumption that the price of contemporary art is biased by the gender of the artist.